Beiträge zur Ichneumonidenfauna Deutschlands. 1. Apechthis Förster, 1869 (Hymenoptera, Ichneumonidae, Pimplinae). - Jacobs, Hans-Joachim (Contributions to Entomology = Beiträge zur Entomologie, 2007)
For the four Apechthis species, which occur in Germany, an identification key and redescriptions are presented. Published faunistic data are evaluated and summarized in a checklist for the German federal states together with newly identified material. Since faunistic data from literature sometimes turned out as not reliable, these have been listed separately. A. compunctor (Linnaeus, 1758), A. quadridentata (Thomson, 1877) and A. rufata (Gmelin, 1790) occur in all German federal states. Most records for these species originate from the period before 1980 since in later years faunistic studies have been conducted only at an insufficient extent. A. capulifera (Kriechbaumer, 1887) is also widely distributed in Germany but it is rare (last hereby checked record from 1935).KeywordsHymenoptera, Ichneumonidae, Pimplinae, Apechthis, Fauna, Deutschland.